Design and develop STEM education in Malaysia: a downdraft gasifier model / Mohd Mahadzir Mohammud, Noor Iswadi Ismail, Nor Azirah Mohd Fohimi, Hazim Sharudin, Theophanny Paula Theresia Rampisela - Mohammud, Mohd Mahazir; Ismail, Noor Iswadi; Mohd Fohimi, Nor Azirah; Sharudin, Hazim; Rampisela, Theophanny Paula Theresia (UiTM Press, 2020)
Design and development of a downdraft gasifier model can be used as a basis to foster STEM (science, technology, engineering and mathematics) education for young generation. Teaching and learning process through model can bridge the gap between STEM disciplines through actual practices, models should be used as a means to promote STEM literacy and the transfer of knowledge and skills between contexts, both in and out of the STEM disciplines. It is therefore imperative that intended model-based pedagogies for STEM education classrooms are further researched, in order to contribute in producing a creative thinking students in STEM educators. Downdraft gasifier used to produce renewable energy. This knowledge is important to young generation. It has been introduced to the secondary school and university. In this paper, a model of downdraft gasifier was designed, developed and tested for the visibility of producer gas output. This model was constructed at lab scaled to decrease the low temperature zone that appear in the actual size. The various parts of the gasifier like the throat, combustion zone, grate, reduction zone, fuel hopper, gas outlet and air inlet were designed. Biomass material source such as rubber wood was selected based on its properties as fuel. Later, the gasifier was ignited by a lighter to prove that the gas produced was a combustible gas. Results showed flares occurred on the gas output. It is proven that the gas ignited when flame is applied to the gas.